PENGARUH GAJI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. ORIGINAL BIRD NEST MEDAN - IDAMRIA HIA; TOGU HARLEN LBN. RAJA; ARISMAN PARHUSIP (JURNAL ILMIAH KOHESI, 2021)
The method used in this study is quantitative with an associative approach. Sampling techniques in this study is probability sampling withsimple random sampling as many as 80 respondents. Data collection is done by disseminating questionnaires to respondents who areemployees of PT. Original Bird Nest Medan. Data analysis techniques use validity test, reliability test, classic assumption test, multiplelinear regression analysis, t test, F test, and R2 determination coefficient test operated through SPSS 16 program. The results of thestudy on variable salaries obtained a calculated t value of 5,584 > t table of 2,000. This shows that partially there is an influence of salaryon employee performance, then the results of t test research on motivation variables obtained a calculated t value of 3,181 > t table2,000. This shows that motivation affects employee performance and collectively affects employee performance. The coefficient of R2determination of 0.565 results showed salary and motivation affected employee performance by 56.5% and the remaining 43.5% wasinfluenced by other variables not included in the study.